Uremic Toxins in Organ Crosstalk - Lowenstein, Jerome; Nigam, Sanjay K. (Frontiers in Medicine, 2021)
Many putative uremic toxins—like indoxyl sulfate, p-cresol sulfate, kynurenic acid, uric acid, and CMPF—are organic anions. Both inter-organ and inter-organismal communication are involved. For example, the gut microbiome is the main source of indole, which, after modification by liver drug metabolizing enzymes (DMEs), becomes indoxyl sulfate. Various organic anion transporters (organic anion transporters, OATs; organic anion-transporting polypeptides, OATPs; multidrug resistance-associated proteins, MRPs, and other ABC transporters like ABCG2)—often termed “drug transporters”—mediate movement of uremic toxins through cells and organs. In the kidney proximal tubule, critical roles for OAT1 and OAT3 in regulating levels of protein-bound uremic toxins have been established using knock-out mice. OATs are important in maintaining residual tubular function in chronic kidney disease (CKD); as CKD progresses, intestinal transporters like ABCG2, which extrude urate and other organic anions into the gut lumen, seem to help restore homeostasis. Uremic toxins like indoxyl sulfate also regulate signaling and metabolism, potentially affecting gene expression in extra-renal tissues as well as the kidney. Focusing on the history and evolving story of indoxyl sulfate, we discuss how uremic toxins appear to be part of an extensive “remote sensing and signaling” network—involving so-called drug transporters and drug metabolizing enzymes which modulate metabolism and signaling. This systems biology view of uremic toxins is leading to a new appreciation of uremia as partly due to disordered remote sensing and signaling mechanisms–resulting from, and causing, aberrant inter-organ (e.g., gut-liver- kidney-CNS) and inter-organismal (e.g., gut microbiome-host) communication.